2021
DOI: 10.1093/genetics/iyab171
|View full text |Cite
|
Sign up to set email alerts
|

Translational control of lipogenesis links protein synthesis and phosphoinositide signaling with nuclear division in Saccharomyces cerevisiae

Abstract: Continuously dividing cells coordinate their growth and division. How fast cells grow in mass determines how fast they will multiply. Yet, there are few, if any, examples of a metabolic pathway that actively drives a cell cycle event instead of just being required for it. Here, we show that translational upregulation of lipogenic enzymes in Saccharomyces cerevisiae increased the abundance of lipids and promoted nuclear elongation and division. De-repressing translation of acetyl CoA carboxylase and fatty acid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 83 publications
1
22
0
Order By: Relevance
“…2014). Conversely, we have shown that increased lipogenesis promotes nuclear division (Maitra et al . 2022).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…2014). Conversely, we have shown that increased lipogenesis promotes nuclear division (Maitra et al . 2022).…”
Section: Discussionmentioning
confidence: 93%
“…We had previously reported that increased lipogenesis promotes nuclear elongation and division (Maitra et al . 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations